KEPUASAN KERJA DAN KOMITMEN ORGANISASI PENGARUHNYA TERHADAP TURNOVER INTENTION - Gde Bayu Surya Parwita; Ni Nyoman Suryani; Ni Komang Ayu Adriani (Forum Manajemen STIMI Handayani Denpasar, 2019)
Along with the development of the organization, various things arise related to human resources. Today the high level of employee turnover has become a serious problem for many companies. One of the efforts made by the company to reduce turnover is increasing employee satisfaction with the company, another factor that also influences turnover intention is organizational commitment. This study aims to determine the Effect of Job Satisfaction and Organizational Commitment to Turnover Intention. Respondents in this study were 88 respondents. Analysis tools that are multiple linear regression analysis. The results of this study indicate that job satisfaction and negative organizational commitment to turnover intention.